2009
DOI: 10.1590/s1020-49892009000200004
|View full text |Cite
|
Sign up to set email alerts
|

Quality of cause-of-death statements and its impact on infant mortality statistics in Hermosillo, Mexico

Abstract: More than half (53%) of COD statements in infant death certificates in Hermosillo were inaccurately completed, which may lead to inaccurate interpretation of causes of infant mortality. Systematic assessments of the quality of COD statements may improve the quality of mortality statistics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Agreement at the 2-digit classification level dropped to 50%, a proportion similar to that reported for infant deaths in Hermosillo. 20 In contrast, a study of adults in Brazil found a higher rate of overall agreement (83%; kappa=0.76) at the 3-digit ICD-10 level. However, 30% of the original statements of death were based on autopsy results, which likely increased the accuracy of the original COD.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Agreement at the 2-digit classification level dropped to 50%, a proportion similar to that reported for infant deaths in Hermosillo. 20 In contrast, a study of adults in Brazil found a higher rate of overall agreement (83%; kappa=0.76) at the 3-digit ICD-10 level. However, 30% of the original statements of death were based on autopsy results, which likely increased the accuracy of the original COD.…”
Section: Discussionmentioning
confidence: 90%
“…In 2003, Alvarez et al investigated the quality of underlying cause of death data coded in the vital registry for a sample of infant deaths. 20 That study indicated a need to improve coding to ensure accurate interpretation of infant mortality patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in various countries [7-13], including Mexico [14,15], have assessed the validity of death certification by comparing the underlying cause of death in the medical death certificate with other sources that provide additional information regarding cause of death, such as medical records. In general, these studies indicate that the concordance between causes of death from death certificates and those obtained using other sources vary by place and cause of death.…”
Section: Introductionmentioning
confidence: 99%
“…The information from Latin America comes mainly from studies in Brazil, analyzing the validity and reliability of cause of death registration in specific areas of the country [9,10]. In Mexico, these studies have concentrated on infant deaths [14,15]. To our knowledge, there is no single study in Mexico that has analyzed the reliability of causes of death based on death certificates for a wide range of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…This effect has been described in other countries. 27,28 However, this effect was not observed in all ecological units, which may be explained by the different degrees of structural modification of the records, over time.…”
Section: Discussionmentioning
confidence: 89%